La cooperación internacional, asunto económico y de geopolítica (2014)
With the level of expressions that the International cooperation has had on the different stages of its historical development and the theoretical concepts that support it, this article pretends to give some important elements to explain Why the so-called “international cooperation for development” has not been only an economic issue but also geopolitical, focused basically to satisfy the needs of donor-developed countries. Consequently, it is considered that the topic treated according with the following subdivision of periods: 1945-1990, 1991-2010, may clarify the questions associated to the interest and forces that underlie the moments of its application and also in the institutions that have been created to sustain it.